Epigenetics and Metabolism. Issue 4 (13th February 2015) - Keating, Samuel T.; El-Osta, Assam
Abstract : The molecular signatures of epigenetic regulation and chromatin architectures are fundamental to genetically determined biological processes. Covalent and post-translational chemical modification of the chromatin template can sensitize the genome to changing environmental conditions to establish diverse functional states. Recent interest and research focus surrounds the direct connections between metabolism and chromatin dynamics, which now represents an important conceptual challenge to explain many aspects of metabolic dysfunction. Several components of the epigenetic machinery require intermediates of cellular metabolism for enzymatic function. Furthermore, changes to intracellular metabolism can alter the expression of specific histone methyltransferases and acetyltransferases conferring widespread variations in epigenetic modification patterns. Specific epigenetic influences of dietary glucose and lipid consumption, as well as undernutrition, are observed across numerous organs and pathways associated with metabolism. Studies have started to define the chromatin-dependent mechanisms underlying persistent and pathophysiological changes induced by altered metabolism. Importantly, numerous recent studies demonstrate that gene regulation underlying phenotypic determinants of adult metabolic health is influenced by maternal and early postnatal diet. These emerging concepts open new perspectives to combat the rising global epidemic of metabolic disorders.